Criminal Acts of Narcotics Abuse According to Law Number 35 of 2009 and the Criminal Code - Eka Permana, Benny; Zarzani, T. Riza (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
Narcotics abuse is a serious issue in Indonesia that continues to escalate, causing significant harm to society. Narcotics, which are intended for medical and research purposes, are often misused, leading to profound social, physical, and mental impacts. This study examines the criminal acts of narcotics abuse under Law Number 35 of 2009 and the Indonesian Criminal Code (KUHP) as regulated in Law Number 1 of 2023. Law Number 35 of 2009 introduces strict criminal sanctions as well as rehabilitation for narcotics addicts. Meanwhile, the Criminal Code addresses the classification of criminal acts and the penalties imposed, including life imprisonment and the death penalty for severe offenses. The study aims to explore the legal provisions governing narcotics abuse and identify the differences in legal enforcement between the two regulations. The findings highlight that, despite stringent regulations, the rate of narcotics abuse remains high, indicating a need for a more integrated approach between law enforcement and rehabilitation efforts.